Asymmetric [3+2] Annulations of Propargylic Carbonates and Vinylogous Nucleophiles via a Nickel-Catalyzed Alkenylation Pathway - Zhao, Zhi; Zhu, Lei; Song, Zhao-Li; Qubi, Keji; Ouyang, Qin; Du, Wei; Chen, Ying-Chun (Synlett, 2025)
The alkenylation reaction of propargylic derivatives catalyzed by transition metals represents a powerful synthetic strategy, usually applied in a double-attack mode to access polyfunctional cyclic products. Whereas a few asymmetric alkenylation reactions involving palladium catalysis have been uncovered, we report here that a nonprecious Ni(0)-based chiral complex exhibits superior efficacy in assemblies of a diversity of propargylic carbonates and vinylogous donors. The reactions proceed through consecutive vinylogous activations of nucleophiles, finally giving [3+2] annulation frameworks by a double attack on nickel-activated species of propargylic carbonates. Both N-trifluoroethyl imines from activated ketones and all-carbon-based vinylogous donors can be utilized, and products embedding a 4-methylene-3,4-dihydro-2H-pyrrole core or a 3-methylenecyclopentene framework, respectively, are efficiently constructed with high regio-, diastereo-, and enantioselectivities. The substrate scope is broad, and further synthetic elaborations of the products permit access to more-versatile structures with emerging applications. Density functional theory calculations and control experiments were carried out to elucidate the reaction mechanism.
Keywords: propargylic carbonates; vinylogous donors; nickel catalysis; alkenylation; [3+2] annulation; enantioselectivity